Upregulation of TLR4 mRNA Expression Levels in Broiler Chickens Under Acute Heat Stress - Huang,S (2017)
ABSTRACT Toll-like receptors (TLRs) are well-characterized in mice and rats, but little is known on their role in broiler chickens during acute heat stress (AHS). The aim of the present study was to estimate the change in TLR4 mRNA expression in the liver, kidney's pleen, heart, and small intestine of broiler chickens under AHS. A total of 240 healthy Arbor Acres (AA) broiler chickens were randomly divided into four groups: control group (22±1°C; 0h), HS2, HS5 and HS10 (38±1°C; 2h, 5h and 10h of heat stress, respectively). As AHS duration increased, TLR4 mRNA expression slightly decreased at HS2 and HS5, but was dramatically elevated in HS10 (p<0.001) compared with the control group in the small intestine, as well as in the spleen at HS2 (p=0.001) and HS10 (p<0.001). The mRNA expression levels of TLR4 significantly increased in the liver, heart, and kidneys (p<0.001) at HS10, and in the kidneys at HS5 (p=0.003). It is found that TLR4 mRNA expression at HS10 in different organs was significantly higher (p<0.001) compared with HS2 and HS5. The results of the present study suggest that AHS may modulate the functional responses of the liver, kidney, spleen, heart, and small intestine of broilers by regulating TLR4 mRNA expression.